Analisis Pengenalan Bendera Negara Rumpun Melayu Menggunakan Metode Feed Forward Neural Network - Santoso, H; Murdianto, D (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
An analysis was made on the digital image recognition system for four Malay family countries’ national flags. These countries are Indonesia, Malaysia, Singapore and Brunei Darussalam. The purpose of this study is as a first step in training the Artificial Intelligent system in distinguishing four Malay family countries based on the colors and motifs of the flags on a digital map. The process of analyzing and training the flag recognition used the Feed Forward Neural Network (FFNN) method. The result showed that the use of 4 Hidden Layers, as well as the use of 0.5 Learning Rate, gave the ability to correctly recognize the image of the flag where the accuracy of the presentation reached an average of 74.15%.